2002
DOI: 10.1089/089771502320914642
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Matrix Metalloproteinase-9 and Attenuation of Edema via Inhibition of ERK Mitogen Activated Protein Kinase in Traumatic Brain Injury

Abstract: Emerging data suggest that matrix metalloproteinase-9 (MMP-9) plays a critical role in the pathophysiology of brain injury. However, the regulatory mechanisms involved in vivo remain unclear. In this study, we focus on a mitogen activated protein kinase (MAPK) pathway that may trigger MMP-9 after traumatic brain injury. We aim to show that inhibition of the extracellular signal regulated kinase (ERK) would attenuate MMP-9 levels, reduce blood-brain barrier damage, and attenuate edema after trauma induced by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 54 publications
4
69
0
Order By: Relevance
“…Inhibition of ERK1͞2 can reduce neuronal death in several settings known to cause extensive PARP-1 activation (17,19,31). Here we show that ERK1͞2 activation is required both for PARP-1 activation and for PARP-1-induced neuron and astrocyte death.…”
Section: Discussionmentioning
confidence: 56%
“…Inhibition of ERK1͞2 can reduce neuronal death in several settings known to cause extensive PARP-1 activation (17,19,31). Here we show that ERK1͞2 activation is required both for PARP-1 activation and for PARP-1-induced neuron and astrocyte death.…”
Section: Discussionmentioning
confidence: 56%
“…Contrasting effects have also been described for ERK. Whereas ERK activation prevented apoptosis after growth factor withdrawal in cerebellar neurons and PC12 cells, 18 our laboratory 13,24,25 and others 26,27 have shown that ERK inhibition protected against cortical neuronal injury. Overall, the literature suggests that contributions of individual MAP kinases depend on the cell types and the nature and severity of the insult involved.…”
Section: Discussionmentioning
confidence: 82%
“…MAP kinase signaling pathways are known to play key roles in cytoplasmic-nuclear signaling transmission in response to various extracellular stimuli, resulting in the production of cytokines, tissue damage, and cell death (21,25). In primary cultured hepatocytes, hyposmotic stress activates ERK1/2 and p38 phosphorylation (20).…”
Section: Discussionmentioning
confidence: 99%